Magnetic Resonance Imaging of Congenital Heart Disease - Syed, Mushabbar A.; Mohiaddin, Raad H.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Over past two decades, cardiac magnetic resonance (CMR) has come to occupy an ever more important place in the assessment and management of patients with congenital heart defects (CHD) and other cardiovascular disorders. It offers an ever-expanding amount of information about the heart and circulation, provides outstanding images of cardiovascular morphology and function, is increasingly being used to detect pathologic fibrosis, and has an expanding role in the assessment of myocardial viability. Despite its impressive clinical performance, its limitations and weaknesses also need to be clearly understood. Magnetic Resonance Imaging of Congenital Heart Disease is an excellent foundation for any reader not familiar with the field whether they are imagers or clinicians who deal with cardiovascular disease. It also describes the technical details of MRI techniques to help the clinician understand the most important elements of CMR in assessing and managing their patients. In creating the book, the editors have assembled a world-renowned panel of contributors to review the use of CMR in CHD and make it accessible to those working in the field and to those who use the information derived from CMR in their clinical practice.
Foreword -- List of Contributors -- General Principles of Cardiac Magnetic Resonance Imaging -- MRI Safety -- Introduction to Congenital Heart Disease Anatomy -- Venoatrial Abnormalities -- MRI of Septal Defects -- Right Ventricular Anomalies -- Tetralogy of Fallot -- Ebstein$1 (Bs Anomaly and Other Tricuspid Valve Anomalies -- Abnormalities of Left Ventricular Inflow and Outflow -- Single Ventricle and Fontan Procedures -- Transposition of Great Arteries -- Aortic Anomalies -- Inherited Cardiomyopathies -- Coronary Artery Anomalies -- Pericardial Diseases -- Cardiac Tumors -- Pediatric Cardiovascular Magnetic Resonance -- Interventional Cardiovascular Magnetic Resonance -- Emerging Roles for Cardiovascular Magnetic Resonance in Adult Congenital Heart Disease Electrophysiology.s
Keywords: Medicine; Radiology, Medical; Cardiology; Heart -- Surgery; Medicine & Public Health; Cardiology; Imaging / Radiology; Cardiac Surgery